The Effect on Job Satisfaction and Stress of the Perceptions of Violence Climate in the Workplace - Aytac, Serpil; Dursun, Salih (Mediterranean Journal of Social Sciences, 2011)
The concept of violence climate is closely related to safety climate according to the employees’ perceptions of organisationalpolicies, practices and procedures directed towards controlling and preventing all kinds of violence in the workplace. This study aimed todetermine the effects of the violence prevention climate on employees’ job satisfaction and stress by determining how they perceive thedimensions of the violence climate. The study was conducted on 118 health workers in a public hospital in Turkey. The study used the18 item Violence Prevention Climate scale developed by Kessler et al (2008) translated into Turkish. The measurements consist of the 3dimensions of policies and procedures, practices and responses and pressure for unsafe practices. According to the results obtained from theresearch, while a positive significant relationship was determined between all the subdimensions of violence prevention climate and jobsatisfaction, no significant relationship was found between the violence prevention climate and the employees’ stress and anxiety levels.Moreover, a significant negative correlation was determined between depression and the violence prevention climate subdimensions ofpolicies and procedures and practices and responses.